Keying Into Ambient Music: Attending to Soundscapes as Phenomenological Practice - Paauw, Elk (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2026)
Ambient music by its very nature is an embodied multi-sensory experience and radical ecological relation that takes up non-human interlocutors by centering sound as an object of inquiry, placing the listener in conversation with plants, animals, weather systems, physical objects, and architecture as interpenetrating subjects-in-space. Using Helen Fielding’s recent work Cultivating Perception Through Artworks as method, “Keying into Ambient Music” is a zine detailing how to engage in a phenomenological reading of ambient music to “key into” one’s surroundings and open up one’s mind relationally to our environment and non-human subjects. This engagement is explored visually as a comic as well as sonically, with an inter-media blend of the physical book as an art object, coupled with a digital suggested listening playlist, an appendix with a poem by Richard Brautigan, and an exercise from Pauline Oliveros’ Software for People, all of which acts as a jumping-off point for the reader/listener to kickstart their own phenomenologically-motivated ambient music practice.The zine’s starting blocks are Matt Evans’ 2020 album “New Topographics” and subsequent liner notes, an examination of how ambient music decenters the human subject as listener and instead makes the content of the music the act of listening itself. Through the digitization of the song-writing process through contact recordings of the artist physically writing translated into synthesized sounds, Evans uses this “sonic residue” as musical subject, connecting tactile sensation, digital archive, and auditory perception to create a “new topographics” of sound (Evans). This impulse situates Evans as taking up two different traditions in ambient music, Kankyou Ongaku or “environmental music” and Pauline Oliveros’ Deep Listening. Kankyou Ongaku, extending from the late 1960’s to early 70s New Age and avant-garde movements in Japan, uses architecturally-situated soundscapes to open up the listener to their environment. This movement collectivizes the music listening experience as a happening between inter-penetrating subjects that include manmade structures, fauna, and foliage, as well as humans. An adjacent movement is Pauline Oliveros’ Deep Listening, a musical practice developed in the late 1980’s as a school of thought focused on engaging in and developing sonic meditations and collective improvisations with the goal of “keying into” one’s environment through highly concentrated, reflective listening. By connecting to one’s acoustic surroundings, deep listening focuses the listener using mindfulness and intentionality to the relationality between human, nonhuman, and artificial forces, expanding one’s “boundaries of perception” (Oliveros). From these musical practices, I then explore the political potential of ambient music in unfolding relations between human and nonhuman subjects. Keying into ambient music can foster recognition of the interconnection of all beings and how to attend to that connection, which can work to dissolve the “anthropocentric ego” (Fielding 281). In surviving against late-stage capitalism and the destruction of our planet, keying into relations between nonhuman beings can forge new paths of resistance and revolt against the status quo of climate denial and inaction, and ambient music is just one tool we can use to build awareness of our interconnectedness and thus open up new ways of being.